Problems and Prospects of Sustainable Development of Mountain Tourism in Modern Conditions - Ibrahimova Sadaqat Veli; Mamedova Sevda Binyat; Temirova Zoxida (BIO Web of Conferences)
This article examines the impact of mountain tourism on mountainous regions, identifying its positive and negative aspects. It examines the popularity of mountain destinations among tourists and their attractiveness due to natural landscapes, culture and sporting events. It is emphasized that unsustainable tourism can negatively affect the environment and public well-being. The development of sustainable tourism practices in mountainous areas, especially in peripheral regions, is considered, taking into account environmental and socio-economic sustainability. Tourism is recognized as one of the priority areas of the economy in Azerbaijan. Tourism has undergone many changes since its inception to the present day. Initially, they concerned its form and content and were associated with the way in which tourist needs were met, which led to the need for an in-depth study and analysis of the tourism economy. The formation of tourism began with its consistent development both qualitatively and quantitatively. During this period, the importance of tourism for the development of the national economy began to be revealed. In modern society, tourism is an integral part of the lives of citizens and at the same time an important type of economic activity. The importance of tourism is difficult to overestimate, since tourism contributes to employment and economic growth of the country, development of infrastructure, preservation and enhancement of the cultural and natural wealth of the countries of the world. This article examines the impact of mountain tourism on mountainous regions, reveals its positive and negative sides. It examines the popularity of mountain destinations among tourists and their attractiveness due to natural landscapes, culture and sports events. It is emphasized that unsustainable tourism can negatively affect the environment and the well-being of the population. The development of sustainable tourism practices in mountainous areas, especially in peripheral regions, is considered, taking into account environmental and socio- economic sustainability. Tourism is recognized as one of the priority areas of the economy in Azerbaijan. Tourism has undergone many changes since its inception to the present day. Initially, the main attention was paid to the form, content and methods of satisfying tourist needs, which necessitated a deep study and analysis of the tourism economy. The formation of tourism began with its consistent development both in qualitative and quantitative terms. During this period, the importance of tourism for the development of the national economy began to be revealed. In modern society, tourism is an integral part of citizens' lives and at the same time an important type of economic activity. The importance of tourism is difficult to overestimate, since tourism contributes to employment and economic growth of the country, development of infrastructure, preservation and enhancement of the cultural and natural wealth of the countries of the world.